(untitled) (Conferencea, 2022)
Great verbal skill, successful style and lyrics made the form of Hafiz’s works projected onto a polysemantic content, when in his poetry the rich form really expressed the multidimensional content. One of these elements - poetic oppositions are considered in this article.